Black Pepper (Piper nigrum) Alleviates Oxidative Stress, Exerts Potential Anti-Glycation and Anti-AChE Activity: A Multitargeting Neuroprotective Agent against Neurodegenerative Diseases - Himadri Sharma; Niti Sharma; Seong Soo A. An (MDPI AG, 2023)
Neurodegenerative diseases (NDs) are a family of disorders that cause progressive structural and functional degeneration of neurons. Among all the organs in the body, the brain is the one that is the most affected by the production and accumulation of ROS. Various studies have shown that an increase in oxidative stress is a common pathophysiology for almost all NDs, which further affects various other pathways. The available drugs lack the wide spectrum necessary to confront these complexities altogether. Hence, a safe therapeutic approach to target multiple pathways is highly desirable. In the present study, the hexane and ethyl acetate extracts of Piper nigrum (black pepper), an important spice, were evaluated for their neuroprotective potential in hydrogen peroxide-induced oxidative stress in human neuroblastoma cells (SH-SY5Y). The extracts were also subjected to GC/MS to identify the important bioactives present. The extracts exhibited neuroprotection by significantly decreasing the oxidative stress and restoring the mitochondrial membrane potential in the cells. Additionally, the extracts displayed potent anti-glycation and significant anti-Aβ fibrilization activities. The extracts were competitive inhibitors of AChE. The multitarget neuroprotective mechanism displayed by Piper nigrum indicates it as a potential candidate in the treatment of NDs.